¡CONGA NO VA! LOS GUARDIANES DE LAS LAGUNAS: DEFENDIENDO LA TIERRA, EL AGUA Y LA LIBERTAD EN CAJAMARCA, PERÚ - Isla, Ana (2017)
The Guardians of Conga Lagoons in Cajamarca region is a case study of an environmental justice movement born in 1999 against Yanacocha open-pit mining of Newmont Mining Corporation, Buenaventura and the World Bank. These corporations hope to move on to Minas Conga as their next project, as a result this movement has intensified its activities since 2011. The article shows the defence of land, water, and freedom by Water Protectors. By focusing on women and men subsistence farmers, Indigenous people and civil society participation, it brings to the forefront three moments of the struggle, first the defence of the land, second, the water protection, and third, freedom struggle. As a result, they have been suffering police and military presence, repression, harassment, fiscal persecution, illegal detentions, prison and death.